The effect of monetary policy on systemic bank funding stability - Maximilian Grimm (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2024)
Does monetary policy affect funding vulnerabilities of the banking system? I show that contractionary monetary policy shocks cause an aggregate outflow of retail deposits and an inflow of non-core market-based funding. Using a newly constructed worldwide dataset covering the liability structure of banking systems at monthly frequency, I demonstrate that a growing reliance on wholesale funding is associated with increasing risks of financial instability and subsequent contractions in lending and real activity. I rationalize this effect of monetary policy on banks' funding structure and ultimately on financial stability risk in a model where profit-maximizing banks do not internalize the heightened systemic risk stemming from the rise of runnable debt in the system. This paper shows that monetary policy has direct consequences for financial stability by changing the liability structure of the banking sector.
Keywords: E44; E52; E58; G01; G21; N10; N20; 330; monetary policy; bank funding; banking fragility